(untitled) (Research, Society and Development, 2025)
Fungi of the genus Trichoderma are known for their activity as plant growth promoters. This study aimed to evaluate the morphological responses of Eucalyptus plants inoculated with Trichoderma harzianum UFT-25. The experiment was developed in a completely randomized design with two treatments: non-inoculated (control) plants and plants inoculated with T. harzianum UFT-25 with ten replicates. The isolate was developed in 50 mm Petri dishes containing a potato, dextrose, and agar (PDA). All plates were incubated in a biochemical oxygen demand (BOD) chamber at 25 ± 2 ºC with a photoperiod of 12 h for seven days. Plants were inoculated by spraying the fourth, fifth, and sixth fully expanded leaves with a suspension of T. harzianum UFT-25 conidia. Control plants received an application of autoclaved distilled water containing 0.02% (v/v) Tween 80. Analysis of the results revealed a significant difference between the treatments in terms of height, diameter, leaf and branch numbers, dry mass, and chlorophyll. T. harzianum UFT-25 stimulated greater growth in the inoculated plants than control plants at 15, 30, 45, and 60 d. The inoculated plants have been shown an increase of 16.19% in the shoot dry mass and 51.65% in the root dry mass. These results open new avenues for exploring the potential of T. harzianum UFT-25, proving its efficiency in promoting the growth of Eucalyptus plants. Thus, the use of this fungus can contribute to the reduction of inputs, such as fungicides and fertilizers, promoting greater sustainability in forestry production.